Gastrin stimulates pancreatic cancer cell directional migration by activating the Gα12/13–RhoA–ROCK signaling pathway - Mu, Ganggang (2018)
The mechanism by which gastrin promotes pancreatic cancer cell metastasis is unclear. The process of directing polarized cancer cells toward the extracellular matrix is principally required for invasion and distant metastasis; however, whether gastrin can induce this process and its underlying mechanism remain to be elucidated. In this study, we found that gastrin-induced phosphorylation of paxillin at tyrosine 31/118 and RhoA activation as well as promoted the metastasis of PANC-1 cancer cells. Depletion of Gα12 and Gα13 inhibited the phosphorylation of paxillin and downstream activation of GTP-RhoA, blocked the formation and aggregation of focal adhesions and facilitated polarization of actin filaments induced by gastrin. Suppression of RhoA and ROCK also exhibited identical results. Selective inhibition of the CCKBR–Gα12/13–RhoA–ROCK signaling pathway blocked the reoriented localization of the Golgi apparatus at the leading edge of migrated cancer cells. YM022 and Y-27632 significantly suppressed hepatic metastasis of orthotic pancreatic tumors induced by gastrin in vivo. Collectively, we demonstrate that gastrin promotes Golgi reorientation and directional polarization of pancreatic cancer cells by activation of paxillin via the CCKBR–Gα12/13–RhoA–ROCK signal pathway.